2008
DOI: 10.1186/1476-4598-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of metallothioneins (MTs) 1, 2, and 3 in response to zinc treatment in human prostate normal and malignant cells and tissues

Abstract: Background: The disturbance of zinc homeostasis featured with a significant decrease of cellular zinc level was well documented to associate with the development and progression of human prostate malignancy. We have previously reported that zinc treatment induces prostate malignant cell apoptosis through mitochondrial pathway. Metallothionein (MT) is a major receptor/donor of zinc in the cells. However, the studies on the expression of MT in association with the prostate pathological and malignant status are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 37 publications
2
47
0
4
Order By: Relevance
“…S20) (54). Under these conditions, no statistically significant increase in fluorescence intensity was observed.…”
Section: Zp1-tpp Is Sequestered In Endosomes/lysosomes and Unable Tomentioning
confidence: 85%
“…S20) (54). Under these conditions, no statistically significant increase in fluorescence intensity was observed.…”
Section: Zp1-tpp Is Sequestered In Endosomes/lysosomes and Unable Tomentioning
confidence: 85%
“…With respect to the MT relation to zinc ions, whose metabolism is abnormal in the prostate tumor tissue, MT participation on pathogenesis of malignant disorder can be expected [45][46][47][48][49][50][51][52][53]. To date, there is no evidence in the literature determining metallothionein level in 22Rv1 and PNT1A cell lines, however, there were done some experiments describing behaviour of RWPE-1 cell line, which revealed similarities of behaviour of this cell line with prostate tissue [54] as well as in the case of PC-3 cell line [55]. Moreover, it was found that MT was up-regulated under hypoxia in prostate cancer cells (LNCaP and PC-3) and overexpressed in prostate cancer tissue and residual cancer cells after androgen ablation therapy [56].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that nuclear MT expression could protect the DNA in ovarian cancer cells from the toxic effect of cisplatin treatment [16] . On the other hand, underexpression of MT has recently been observed in prostate [15] and primary human hepatocellular carcinomas [12] . MT-1E, MT-1G, MT-1X and MT-2A genes were also found to be downregulated in papillary thyroid carcinoma [14] .…”
Section: Introductionmentioning
confidence: 99%
“…MT-1 and MT-2 are expressed ubiquitously, whilst MT-3 and MT-4 are expressed specifically in certain cell types. Aberrant expression of MT has been found in various human cancers, including cancers of the gall bladder [8] , ovary [9] , B-cell lymphomas [10] , breast [11] , liver [12] , skin [13] , papillary thyroid carcinoma [14] and prostate [15] . It has been suggested that MT overexpression could protect cancer cells from free radical-induced DNA damage and lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%